Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s10930-013-9506-1
|View full text |Cite
|
Sign up to set email alerts
|

Homology Modeling, Molecular Docking and DNA Binding Studies of Nucleotide Excision Repair UvrC Protein from M. tuberculosis

Abstract: Mycobacterium tuberculosis is a Gram positive, acid-fast bacteria belonging to genus Mycobacterium, is the leading causative agent of most cases of tuberculosis. The pathogenicity of the bacteria is enhanced by its developed DNA repair mechanism which consists of machineries such as nucleotide excision repair. Nucleotide excision repair consists of excinuclease protein UvrABC endonuclease, multi-enzymatic complex which carries out repair of damaged DNA in sequential manner. UvrC protein is a part of this compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Assessment of secondary structure prediction of different isoforms gives an idea about structural pattern from the protein sequences in terms of helix, sheets and coils. For this Psipred program was used to observe the variation among different isoforms. ARNTP1 variant was found to attain mostly alpha helical conformation while ARNTP3 shows both strand and helix form (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of secondary structure prediction of different isoforms gives an idea about structural pattern from the protein sequences in terms of helix, sheets and coils. For this Psipred program was used to observe the variation among different isoforms. ARNTP1 variant was found to attain mostly alpha helical conformation while ARNTP3 shows both strand and helix form (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking studies have been found useful to understand interactions between enzymes and ligands [34][35][36][37]. Thus, molecular docking studies were carried out between carotenoid dehydrosqualene synthase (PDB ID: 3ACX) and pyrano[2,3-d]pyrimidinediones using Patch dock server [38,39].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…For predicting the function of recombinant protein, the interaction of various ligands with the recombinant and natural protein is investigated using MVD (Molegro Virtual Docker) software [11]. As a result of this ligand-protein connection by providing the MolDock score, interaction is estimated.…”
Section: Function Prediction Of Normal and Mutant Lipase Proteinsmentioning
confidence: 99%